Planning Urban Manufacturing, Industrial Building Typologies, and Built Environments: Lessons From Inner London - Ferm, Jessica (2021)
Despite concerns about the loss of industry, industrial land, and buildings in high-value post-industrial cities, there is concurrently a renewed enthusiasm around the potential of “new” urban manufacturing and its contribution to the socio-economic diversity of cities. Yet, little is known about how planning policy can best support the retention and growth of urban manufacturing. To advance this agenda, this article proposes that we need a better understanding of industrial building typologies and resultant urban form. Using concepts developed by Julienne Hanson to analyse residential morphologies undergoing transformation under modernism, we apply these concepts to investigate the industrial, mixed-use contexts in two areas of London with concentrations of urban manufacturing—Hackney Mare Street and Old Kent Road. The research presented examines how both areas have evolved historically to produce distinctive urban tissues and a range of industrial building typologies. The article reveals that, despite territorial similarities in the late 19th century, the mixed land uses and smaller plot sizes of Hackney Mare Street have allowed for a more resilient development pattern, whereas the greater separation of land uses, large plot sizes, and inward-facing development in the Old Kent Road has facilitated its reimagination for large-scale regeneration. We conclude that greater attention needs to be paid to the relationship between urban manufacturing and built urban form if policies that aim to protect or support the revival of manufacturing in cities are to avoid negative unintended consequences.